Analisis Sebaran Bakteri Coliform Di Kanal A Kuala Dua Kabupaten Kubu Raya - Ahmad Mulyadi, Syaeful Arifudin, Siti Khotimah, (Jurnal Protobiont, 2014)
Canal A Kuala Dua is one of the water source used in daily activities by the society lives along that river banks. The occurence of markets and inhabitans activities such as bathing and washing can affect the water quality of Canal A Kuala Dua due to the disposals entering the water body. One of the bioindicator used to detect water pollution is coliform bacteria. The purpose of this research was to find out the dispersion pattern of coliform bacteria when ebb and flow occurs in Canal A Kuala Dua. The Research was done in November 2011 through March 2012. Sampling was done at 9 stations along Canal A Kuala Duan when the ebb and flow occurred. The density of coliform bacteria was calculated by MPN method and Escherichia coli qualitative test was done by IMVIC test. Statistics sofwares such as Microsoft Excel, SPSS 15 (t test), and Arcgis 10.1 were used in data anylisis. Based on its use, Canal A Kuala Dua is categorized into class C. Average values of coliform bacteria densities in Canal A Kuala Dua are 74,249 x 103 MPN/100 mL when the uptide occurs and 59,259 x 103 MPN/100 mL when the downtide occurs.